EFEKTIVITAS SANKSI HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA LINGKUNGAN HIDUP PADA KASUS POLUSI AIR - Liana, Santi; Miranda, Desi; Putri, Cut Juria (PT Metrum Karya Mandiri, 2024)
The impact of this environmental damage is very large and tends to be detrimental to us as living creatures who will continue to develop and need a comfortable and clean environment for a sustainable living process. Water pollution is a highly discussed issue considering that water is a source of life for every living creature. This water pollution occurs due to excessive use of chemicals and the accumulation of waste that cannot be managed which ultimately flows into waterways. Company activities that dispose of waste carelessly or channel waste into rivers are also the cause of water pollution. The research method used in this research is normative juridical research, namely examining law from an internal perspective with the object of research being legal norms. The effectiveness of legal sanctions against perpetrators of environmental crimes in cases of water pollution in accordance with Law No. 32 of 2009 concerning Environmental Protection and Management has not been able to be carried out optimally, due to lack of commitment by law enforcers, inadequate facilities and infrastructure and inadequate factors. awareness of protecting and preserving the environment by the community itself.